A GIS-Based Analysis of Agricultural Land Use Change in the Mississippi Delta. - Olson, Lindsay M. (My University, 2009)
The Mississippi Delta is not actually a delta, but is an alluvial plain located between in the Yazoo and the Mississippi Rivers. The delta has historically been used for cotton and rice farming due to its superb agricultural qualities. This project will illustrate how land use has changed from agriculture to other types of land use over the last decade of the 20th century, specifically between the years 1992 and 2001.
Color poster with text, images, and maps.
Keywords: Agriculture--Mississippi-Delta (Region); Land use--Mississippi--Delta (Region); Delta (Miss. : Region)--Geography; Posters